A Personal leadership statement (2023)
Leadership, an enduring concept since ancient times, enables individuals to guide social groups in evolution and empowerment within social causes. However, because of the diversity of definitions from various authors, confusion has emerged, especially in education, where leadership may be erroneously linked to authority or management. This personal leadership statement will guide us to develop our future teaching practices as transformational leaders. Therefore, it contains our assumptions, beliefs, approach, and aspirations for the future. This paper is the learning product of the diploma course in Lifelong Professional Development: Empowering Foreign Language Teachers. Consequently, this statement aims to lead the educational field with innovative and transformational ideas by shaping the overall success and development of schools through empowerment. Then, it is expected to have a profound impact on effective plans and build values in education within the role of empowered teacher-leaders.